Analisis Kemauan Pemuda Untuk Memimpin Ibadah Di Jemaat Filadelfia Babang - Juniati Saledok; Niel Parinsi; Alce Mariani Labito (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2023)
Youth are expected to play a vital role in reviving, renewing and sustaining church traditions and developing a new vision for the church in a changing world. However, many youths are reluctant to participate in this process, particularly in Jemaat Filadelfia Babang. This article explores the reasons behind this lack of engagement, focusing on the concept of willpower and how this relates to motivation and self-confidence. The research method used is quantitative with a survey approach. The results show the importance of social support in building a person's confidence in leading worship. The article also discusses the importance of social support in building one's confidence in leading worship. This article explains willpower and self-confidence as interrelated and complementary concepts in encouraging the active involvement of youth in church activities. The article also discusses theories that explain the relationship between willpower and motivation and the relationship between willpower and self-confidence.